Epidemiology of common hand conditions - Lane, JCE (2021)
This thesis aims to appraise and analyse a variety of routine data sources to better understand their use in surgical epidemiology. The clinical focus of the thesis is to use real world data to generate a better understanding of the benefits and risks of surgery for carpal tunnel syndrome (CTS) and base of thumb osteoarthritis (BTOA) in routine clinical practice, and of the role of female hormones in the aetiology of these conditions.